Effect of yellow sweetclover (Melilotus officinalis) hay compared with Lucerne (Medicago sativa) hay on carcass characteristics and meat quality of male goat kids - Lahkim Bennani Mouad; Aarab Ahmed; Jaber Abdelaziz; Acherkouk Mohamed; Ayadi Mohammed (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: Melilotus officinalis is a plant that grows naturally in northwestern Morocco and could become a promising alternative. The study was carried out to investigate the effects of M. officinalis hay on growth performance, carcass characteristics, and meat quality of goat kids in northern Morocco compared to Medicago sativa. Materials and Methods: Eighteen 3-month-old male "Beni Arouss" goat kids have been divided similarly into two groups. The control group (Luc) received lucerne hay, and the test group (YSClov) received yellow sweetclover hay, both supplemented with concentrate. Average daily gain and dry matter intake were determined during the experiment. After 99 days, goat kids were weighed, and carcass characteristics were determined. Meat quality was evaluated using samples from the semimembranosus (SM) and longissimus thoracis muscles. Results: The addition of YSClov significantly increased ash content (p < 0.001) and fat content (p < 0.01), reduced water holding capacity (p < 0.01), and SM pH 24 (p < 0.05). The YSClov meat was significantly more tender than the Luc meat, with corresponding values of 8.20 and 11.80 kg/ cm² (p < 0.05), while the Luc meat was more tender when cooked. No significant effect was found for the other parameters. The YSClov meat is richer in desirable fatty acids (DFA), while the Luc meat appears to be richer in omega-3 DFA(p < 0.01). Conclusion: Melilotus officinalis hay showed promising results in intramuscular fat, protein content, tenderness, DFA content, and similar growth performance compared to conventional feeds. [J Adv Vet Anim Res 2022; 9(4.000): 617-624]